2021
DOI: 10.3389/fneur.2021.687134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Risk Factors, Safety, and Efficacy Outcomes of Mechanical Thrombectomy in Posterior vs. Anterior Circulation Large Vessel Occlusion

Abstract: Background and Purpose: It is believed that stroke occurring due to posterior circulation large vessel occlusion (PCLVO) and that occurring due to anterior circulation large vessel occlusion (ACLVO) differ in terms of their pathophysiology and the outcome of their acute management in relation to endovascular mechanical thrombectomy (MT). Limited sample size and few randomized controlled trials (RCTs) with respect to PCLVO make the safety and efficacy of MT, which has been confirmed in ACLVO, difficult to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Neurological deficits caused by PCCI was described as catastrophic with severe disability and death. [ 56 ] Due to the rarity of PCCI cases, it is challenge for obtaining a large sample size to study the prognosis of those patients. It is essential to deep understanding more detailed prognostic factors of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurological deficits caused by PCCI was described as catastrophic with severe disability and death. [ 56 ] Due to the rarity of PCCI cases, it is challenge for obtaining a large sample size to study the prognosis of those patients. It is essential to deep understanding more detailed prognostic factors of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In clinic, when cerebral infarction occurs in posterior circulation, it is still very difficult to deal with. Neurological deficits caused by PCCI was described as catastrophic with severe disability and death [56] . Due to the rarity of PCCI cases, it is challenge for obtaining a large sample size to study the prognosis of those patients.…”
Section: Discussionmentioning
confidence: 99%
“…The highly effective reperfusion using multiple endovascular devices (HERMES) collaboration ( 21 ), for example, the time interval between randomization and reperfusion was 20 min later in patients who had GA vs. patients who had non-GA during EVT in anterior circulation ischemic stroke. However, in the present study, puncture to reperfusion times were significantly longer in the GA group that did not confer a disadvantage to patients with VBAO compared to non-GA. A recent meta-analysis showed that in spite of the longer onset-to-EVT and onset-to-groin puncture times in VBAO, favorable functional outcome at 90 days in VBAO was comparably no difference just as in anterior circulation large vessel occlusion during EVT ( 22 ). This could be supported by the hypothesis that benefit of recanalization is less time-dependent in VBAO than in anterior circulation large vessel occlusion due to the anatomical vascular layout of the brainstem being different from that in usual anterior circulation stroke ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…All in all, the majority of observational studies showed a benefit of EVT in LVO posterior circulation strokes [9][10][11][12][13][14]. A recent meta-analysis of 16 studies indicated comparable rates of successful reperfusion and good clinical outcome comparing anterior and posterior circulation strokes [15]. However, two large prospective observational studies did not support the superiority of EVT over IVT in patients with BAO, demonstrating relatively poor outcome despite successful reperfusion [2,16].…”
Section: Introductionmentioning
confidence: 99%